Characteristics of condylar fracture in Dr. Hasan Sadikin Central General Hospital, Bandung from 2020-2024. - Wicaksono, Septyan Dwi; Sjamsudin, Endang; Oli'i, Eka Marwansyah; Utomo, Hafidh Seno Radi (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: Condylar fractures are among the most common mandibular fractures resulting from maxillofacial trauma, primarily caused by traffic accidents, occupational injuries, and sports activities. These fractures can lead to complications such as pain, mandibular deviation, malocclusion, and pathological changes in the temporomandibular joint. This study aims to identify the characteristics of condylar fractures in the Oral Surgery Department of Dr. Hasan Sadikin General Hospital Bandung from 2020 to 2024.Method: A retrospective analysis was conducted using medical records of maxillofacial trauma patients. A total of 111 cases were analyzed based on gender, age, occupation, education level, fracture classification, trauma etiology, and management.Result: Results showed that the majority of patients were male (72%), aged 13–24 years (48,6%), students (51,3%), and had a bachelor’s degree as the educational background (49,6%). The AO classification predominantly involved condylar neck fractures (52,3%), with traffic accidents being the leading cause (51,4%). The most common management method was open reduction and interdental wiring (76,6%). Conclusion: These findings highlight the need for targeted road safety education, strict traffic regulations, and improved preventive measures to reduce the incidence of such injuries. Therefore, an effort must be made to improve the completeness of medical record data in order to support more accurate analysis and the implementation of future research involving more comprehensive data collection.